INFLUENCE IMAGE MEDIA TO IMPROVE ENGLISH VOCABULARY - Sudianto; Tuti (TULIP (Tulisan Ilmiah Pendidikan), 2020)
Learning process In addition to an attempt to grant knowledge or transfer of knowledge, but it is also the value of education from one generation to another. Learning is seen from its scope, consisting of several components. Such components include objectives, lesson materials, teaching and learning activities, methods, tools, learning resources or evaluation One way to address the situation is to choose and use good and appropriate media in the learning process in order to help smooth, effective and efficient in achieving learning objectives and addressing the use of Conventional methods and make the learning process more vivid. Thus, directly the interest and learning outcomes of learners in English language learning will also increase and achieve So this can be a task as a teacher how to make students can like English language lessons quickly in the experience with the goal of improving their vocabulary as they study in English in the classroom, now day students are very low in Memorizing and mastery of English vocabulary, one of the ways we can use the image media method, memorizing is one of the ways that we can use so that students are Easier master vocabulary using Image media methods, with this image media tool students will focus to pay attention to every vocabulary listed in the picture besides their easy guess the meaning contained in the picture. in the thesis research entitled "the influence of image media to improve students' English vocabulary. By using literature study research, the writer can understand how the processes to achieve research objectives are seen from previous research journals, where the majority of them discuss the use of image media to improve students' English vocabulary.. There are so many ways and techniques they use to achieve their goals, with the many media that can be applied to make students understand vocabulary easier and easier to memorize English vocabulary by using picture media with so many models that they are not too bored with use of this image media.